A literature review on how tax incentives could assist innovation and SME research ecosystem - Ahmad, Nurazwa; Abdullah, Nor Hazana; Ahmad, Anita; Abu, Ghazali (Global Academic Excellence, 2021)
In an effort to foster the innovation and commercialization ecosystem in Malaysia, the government has introduced various tax mechanisms such as the allocation of funds from tax incentives to provide financial assistance to small and medium-sized enterprises (SMEs). As against large corporations which have substantial research and development budgets to start with, limited capital and financial constraints in SMEs companies hinder their capabilities to fund their own R&D which in turn affect their innovation capabilities. This paper reviews various tax mechanisms and initiatives used by other countries to facilitate the SMEs’ innovation capabilities and how universities collaborate the R&D efforts with industries through grants and incentives. The findings are later compared to the research ecosystem in Malaysia, the government, the policy, and the challenges of implementation. It is concluded that SMEs could benefit from the spill over of funds from tax mechanisms to finance their R&D collaboration. This government-university-industry symbiotic triple helix linkage could create a conducive research ecosystem and benefit the SMEs in innovation capabilities and product commercialization.